2008
DOI: 10.5194/nhess-8-1403-2008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of check dams on debris-flow run-out intensity

Abstract: Abstract. Debris flows are very dangerous phenomena claiming thousands of lives and millions of Euros each year over the world. Disaster mitigation includes nonstructural (hazard mapping, insurance policies), active structural (drainage systems) and passive structural (check dams, stilling basins) countermeasures. Since over twenty years, many efforts are devoted by the scientific and engineering communities to the design of proper devices able to capture the debris-flow volume and/or break down the energy. If… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…Hassanli et al (2009) evaluated the effect of porous check dam location on the retention of fine sediments by field sampling and laboratory analysis in the Droodzan watershed, southern Iran. Remaître et al (2008) used a debris-flow model to evaluate the influence of the number and the location of the check dams on the debris-flow intensity in the Faucon watershed of south French Alps. The results indicated that check dams located near the source area may decrease debris-flow intensity more efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Hassanli et al (2009) evaluated the effect of porous check dam location on the retention of fine sediments by field sampling and laboratory analysis in the Droodzan watershed, southern Iran. Remaître et al (2008) used a debris-flow model to evaluate the influence of the number and the location of the check dams on the debris-flow intensity in the Faucon watershed of south French Alps. The results indicated that check dams located near the source area may decrease debris-flow intensity more efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Yielding only individual predictions and not adequately including qualitative system changes (disruptions, Godet, 2000), deterministic models were found to be only partially useful when trying to predict future states of complex systems. If a sediment dosing system, typically composed of an approaching reach, a deposition basin, an open check dam and an outlet reach is considered, the evolution of the channel bed level in the retention basin during either the increasing or the decreasing part of the hydrograph can be accurately and precisely predicted by deterministic models (Armanini and Larcher, 2001;Miyazawa et al, 2003;Remaître et al, 2008). However, the simultaneous presence of woody debris transport phenomena obstructing the openings (e.g.…”
Section: Background -Exploring Alternative Developments Through Scenamentioning
confidence: 99%
“…A homogeneous erodible soil depth of 2.5 m was selected since there was a lack of information about this or a soil depth map (this depth was also assumed to quantify the release volume). Based on the geological, lithological and morphological description of the area and based on the account of historical data, a soil depth of 2-3.5 m was found to be the value that agrees best with the quantity of entrained material in past events (Remaître et al 2008;Quan Luna et al 2011, 2014. This was also done to assess the performance of the model Fig.…”
Section: Run-out Characterizationmentioning
confidence: 99%